The Process of Vitalizing and Revitalizing Culture-Based Pedagogy in Sámi Schools in Sweden - Balto, Asta Mitkijá; Johansson, Gunilla (International Journal about Parents in Education, 2023)
The Sámi schools provide Sami children an education that also deals with Sami and is equivalent to an education in the Swedish nine-year compulsory school. Both Sámi and Swedish language are used in the Sámi schools. Sámi schools are an option for all parents who claim to be Sámi. The main purpose of this study was to learn, describe, analyse and work with processes aiming to strengthen the Sámi cultural and linguistic competencies within the Sámi school system. Sámi Schools in Sweden and their staff have not yet been able to reconstruct a Sámi school platform of their own. Teacher education or training of teachers, in Sweden has few adaptations for the appropriate education of teachers working at Sámi Schools. Regardless of this situation, teachers and parents expressed a vision of a Sámi School with cultural sensitivity and that also takes the culture into account in the curriculum and activities.  The idea for the three-year participatory action research project discussed in this paper was initiated by the rectors of two Sámi primary - and preschools in Sweden. The research model and the research objectives of the study were developed together with the teachers, rectors, to some extent the parents and elders. The research project focused on how the Sámi School community could be enabled to activate their cultural knowledge and practices to make them part of the curriculum and the schools’ everyday life. This article discusses how to 1) examine the possibilities for a Sámi-culture-based pedagogy and the conditions required to enable them, and how to 2) recognize challenges, weaknesses and the strengths therein. The research project was conducted in two Sámi schools in Sweden with 115 children, their parents and elders, and 30 teachers as actors in the collaborative, collective process. The rectors and teachers were leading the processes. Results included transforming and integrating Sámi culture and language into pedagogy and curriculum content. Practices were improved. The positive research results were disseminated to both State and Sámi educational and political authorities. The need for a continued Sámi education and competence-building for teachers and staff was highlighted. No actions have yet been taken by the various informed authorities to continue the school development or the capacity building of Sámi teacher’s professional skills.